Practice of Teaching Creative Writing with Text in a High-quality Context for College Students Based on Predictive Analysis Ability of Big Data - Xu, Mo; Li, Yuanyuan (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: With the advent of the digital age, big data has become essential to all walks of life. In digital education, it has become an indispensable part, which can cover the students’ learning progress, learning hours, practice scores, course information, classroom interaction information and so on, which makes the teaching process fully covered and a one-stop learning experience. Big data is essential to promote China’s education to the scientific, systematic, informatization and customization continue to move forward. OBJECTIVES: To further improve the writing ability of college students in China, the systematic learning of big data is integrated into the daily teaching and life of the university so that college students can better embrace this significant data era. METHODS: This paper discusses the analysis of the current situation of college students’ accompanying writing, the problems and improvement methods of college students’ accompanying creative writing, the systematic elaboration of big data, and the method of predictive analysis of big data to explore the practice of teaching college students’ accompanying creative writing in a high-quality context based on the ability of predictive analysis of big data. RESULTS: With the advent of the digital age, big data has become an essential part of various fields. As an even more indispensable part of the digital education field, it can cover students’ learning progress, learning time, practice results, course information, classroom interaction information, Etc., indeed covering the entire education program for a one-stop learning experience. CONCLUSION: For language teachers in colleges and universities, improving the ability of predictive analytics under big data and then integrating it into the teaching practice to cultivate college students with high-quality creative writing skills based on the ability of predictive analytics of big data is the current priority, and is also the goal of colleges and universities to cultivate talents.